PATOMORFOLOGICHESKY ASSESSMENT ETHANOL POISONING AMID ALCOHOLIC LIVER DISEASE - E. N. Travenko; V. A. Porodenko (Кубанский научный медицинский вестник, 2017)
Morphological pattern of alcohol poisoning and its evaluation remains controversial issue to date. In this paper we analyzed and evaluated pathologic features ethanol intoxication in patients with various forms of alcoholic liver disease (ALD).